STUDY OF ETHNO-CARNIVORE RELATIONSHIP IN DHIRKOT, AZAD JAMMU AND KASHMIR (PAKISTAN) - S. S. Bibi; R. A. Minhas; M. S. Awan; U. Ali; N. I. Dar (Journal of Animal and Plant Sciences, 2013)
Human-carnivore conflict is the major issue for the carnivore conservation in Azad Jammu and Kashmir. Due to the habitat degradation of the wildlife, the natural prey of carnivore species is declined resulting into the increased depredation of livestock, which in turn causes the human-carnivore conflicts. This paper presents the results of the study of the human-carnivore relationship in Tehsil Dhirkot, Azad Jammu and Kashmir, Pakistan during 2009-2010. Study was aimed to explore the extent of depredation (injuries and deaths) of livestock and human beings by different carnivore species, estimation of the economic loss of the local villagers, perceptions of the locals and retaliatory killings of carnivores during the last three years. A sum total of 150 affectees were interviewed using structured questionnaires and discussions were made with the local community during 40 surveys conducted in 20 villages of eight union councils of the study area. Three main carnivore species were found to be responsible for livestock killing and human injury. Common Leopard was responsible for the majority (70.8%) of such livestock killing; mainly goats (20%) and donkeys (18%). Jackals were responsible for about 80% of the poultry killings. These livestock depredations by carnivore species lead to a financial loss of about US$ 23529.41 to the local community during 2009-2010. Four persons were also injured during the leopard attacks at Surang, Hill, Munhasa and Sohawa. In response, four leopards were killed by the local community at Ghaziabad, Narakot, Surang and Rangla. Most (85%) of the people dislike predators and about 90%respondents recommended that predators should be conserved in zoos and wildlife parks while 10% respondents were in favor of predator conservation in natural habitat. The study revealed that leopards along with other carnivore species were widely involved in depredation of livestock and has been heavily persecuted by the rural communities. This issue is the major threat to the conservation of large carnivore species. To improve both large carnivore population and local livelihood prospects around study area, conservation and management projects with conflict mitigation strategies should be initiated.
Keywords: Ethno-carnivore relationship; livestock depredation; Azad Jammu and Kashmir; Pakistan